2011
DOI: 10.7882/az.2011.059
|View full text |Cite
|
Sign up to set email alerts
|

The impact on native herpetofauna due to traffic collision at the interface between a suburban area and the Greater Blue Mountains World Heritage Area: an ecological disaster?

Abstract: Vehicle collision resulting in animal mortality is a common daily occurrence, although few studies have considered the impact on herpetofauna in urban areas. Over a 7 year period (2003 -2010), 1.4 km of suburban streets of Falconbridge that interface with the Greater Blue Mountains World Heritage Area, west of Sydney, was surveyed on foot two to four days a week, typically soon after dawn. Over the period a total of 86 reptiles that represented 20 species: 38% of the lizard and 56% of snake species known from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Additionally, this scale provides a broad assessment of urbanization that can provide the framework for future studies of areas within the island as data layers with increased resolution become available. Based on the natural history of P. martini (Van Buurt 2005), as well as mortality studies of other gecko species (Das et al 2007;Schutt 2008;Wotherspoon and Burgin 2011), rivers, roads and urbanized areas were weighted as difficult to pass through, whereas the natural arid bush habitat (mondi) of the island was given the lowest resistance (Appendix 2). Although P. martini will readily colonize walls, this coding of resistance reflects findings by Hughes et al (2015), who found this species to be absent in urban areas away from edge habitats.…”
Section: Spatial Analysesmentioning
confidence: 99%
“…Additionally, this scale provides a broad assessment of urbanization that can provide the framework for future studies of areas within the island as data layers with increased resolution become available. Based on the natural history of P. martini (Van Buurt 2005), as well as mortality studies of other gecko species (Das et al 2007;Schutt 2008;Wotherspoon and Burgin 2011), rivers, roads and urbanized areas were weighted as difficult to pass through, whereas the natural arid bush habitat (mondi) of the island was given the lowest resistance (Appendix 2). Although P. martini will readily colonize walls, this coding of resistance reflects findings by Hughes et al (2015), who found this species to be absent in urban areas away from edge habitats.…”
Section: Spatial Analysesmentioning
confidence: 99%
“…While the low speed, suburban street that Wotherspoon and Burgin (2011) reported on has remained effectively unchanged for more than 20 years, species may become locally extinct as a result of new road development (Lunney et al 2002) while the long-term viability of some vertebrate populations may be compromised (e.g., Jones 2000; Ramp and Ben-Ami 2006).…”
Section: Mountain Biking and Fauna Conservationmentioning
confidence: 99%
“…Mountain biking trails through natural bushland offer an equivalent interface that has the potential to attract animals, particularly reptiles that thermoregulate and expose them to predation and collision with bikers' wheels. For example, over a seven year period, Wotherspoon and Burgin (2011) collected 19 reptile species (33% of the local recorded reptile fauna) as road kill on early morning excursions in Faulconbridge on a suburban road in a 50 km zone that abutted national park. These species are also likely to access trails within the local national park and therefore expose themselves to possible collision if it were a mountain biking trail.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Reptiles, especially species that are habitat specialists, may be particularly sensitive to habitat alteration due to relatively slow dispersal and Diversity 2022, 14, 655 2 of 11 recolonization rates [23,24]. Studies in lizards have suggested that they may be deterred by urban anthropogenic stressors such as noise [25], excess light [26,27], and vehicular traffic [28,29]. While a wide range of studies have begun to emerge on urban lizard morphology, reproduction, physiology, behavior, genetics, learning, and habitat occupancy [30][31][32][33][34][35][36][37][38][39][40][41][42], as well as several current reviews and meta-analyses [36,[43][44][45], many more are needed to better understand the effects of urbanization and other anthropogenic land uses on reptiles.…”
Section: Introductionmentioning
confidence: 99%